Analysis of Construction Requirements For Concrete and Asphalt Pavements on The Temuireng-Jetis Road Section, Mojokerto District - Rusida, Dukha; Oetomo, Wateno; Marleno, Risma (Pelopor Publikasi Akademika, 2025)
This study analyzes the construction requirements for rigid (concrete) and flexible (asphalt) pavements on the Temuireng-Jetis road section in Mojokerto District, focusing on the cost-effectiveness and efficiency of both options. The research compares pavement thickness design, cost, and implementation time using the 2017 Pavement Design Manual (MDPJ) and Pd T-14-2003 standards. Data was collected through field surveys and reports from the Mojokerto District Public Works Office. The findings indicate that rigid pavement, with a 25 cm thickness, offers greater long-term economic advantages compared to flexible pavement due to its superior durability, reduced maintenance needs, and better performance under heavy traffic. Although rigid pavement has higher initial construction costs, it proves more cost-effective over time. Flexible pavement, while cheaper initially, incurs higher maintenance costs and is more prone to damage in high-traffic areas. The study recommends using rigid pavement for roads expected to support heavy vehicles and require extended service life. In conclusion, this research provides valuable insights into selecting the appropriate pavement type based on cost, durability, and long-term benefits, offering practical guidance for policymakers and engineers in Mojokerto and other regions facing similar infrastructure challenges.